Nano-Confined Synthesis of Fullerene Mesoporous Carbon (C60-FMC) with Bimodal Pores: XRD, TEM, Structural Properties, NMR, and Protein Immobilization - Mohammad A Wahab; Farzana Darain#; Azharul Karim; Jorge N Beltramini (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2016)
Nanoconfined synthesized crystalline fullerene mesoporous carbon (C60-FMC) with bimodal pore architectures of 4.95 nm and 10-15 nm pore sizes characterized by XRD, TEM, nitrogen adsorption/desorption isotherm and solid-state NMR, and the material was used for protein immobilization. The solid-state 13C NMR spectrum of C60-FMC along with XRD, BET and TEM confirms the formation of fullerene mesoporous carbon structure C60-FMC. The immobilization of albumin (from bovine serum, BSA) protein biomolecule in a buffer solution at pH 4.7 was used to determine the adsorption properties of the C60-FMC material and its structural changes investigated by FT-IR. We demonstrated that the C60-FMC with high surface area and pore volumes have excellent adsorption capacity towards BSA protein molecule. Protein adsorption experiments clearly showed that the C60-FMC with bimodal pore architectures (4.95 nm and 10-15 nm) are suitable material to be used for protein adsorption.